A 1960MPa grade high-strength multiphase hot-rolled wire rod for bridge cables and a manufacturing method thereof

Through the design of C-Si-Mn-Cr-V components and the rapid quenching of online molten salt, the formation of mesh carbides and abnormal tissues in hot-rolled strips for cables of 1960MPa grade bridges was solved, and high strength, good tissue uniformity and low risk of wire breaking were achieved.

CN119162428BActive Publication Date: 2025-03-28JIANGSU YONGGANG GROUP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411650080.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-28
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The existing hot-rolled strips for cables for 1960MPa grade bridges are prone to form mesh carbides and abnormal tissues while improving strength and drawing performance, resulting in increased brittleness, increased risk of broken wire and unqualified torsional performance.

Method used

The high-strength composite hot-rolled strip designed with C-Si-Mn-Cr-V components is quickly quenched through the online molten salt. First, the molten salt in the front section quickly cools down and enters the coxnitite phase area to inhibit the formation of network carbides. Then, the molten salt in the latter section controls the rapid transformation of high-temperature austenite into bainite tissue, performs short-term tempering, weakens bainite brittleness and improves strong plasticity matching.

Benefits of technology

It effectively avoids the formation of mesh carbides and abnormal tissues, improves the strength and tissue uniformity of the strips, reduces the risk of wire breaking and unqualified torsion, and is suitable for the manufacturing of 1960MPa-level bridge cables.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162428B_ABST
    Figure CN119162428B_ABST
Patent Text Reader

Abstract

The invention relates to a high-strength multiphase hot-rolled wire rod for 1960MPa-level bridge cables and a manufacturing method thereof. After rolling and spinning into a wire rod with a V-containing hypereutectoid chemical composition, the wire rod is subjected to an online molten salt rapid quenching treatment, so that the wire rod first passes through a front-stage molten salt and is cooled at a cooling rate of ≥37°C / s, enters a sorbite phase region from an austenite state, promotes the transformation of part of austenite to sorbite, and then undergoes a rear-stage molten salt cooling isothermal treatment to promote bainite phase transformation and isothermal tempering, and finally is slowly cooled through a roller to obtain a hot-rolled wire rod with a microstructure including a multiphase structure composed of tempered bainite and tempered sorbite. The hot-rolled wire rod can take into account the plasticity of the wire rod and further improve the strength and uniformity of the wire rod, so as to achieve a tensile strength of 1420-1470MPa and a cross-sectional shrinkage of 39%-44%, thereby improving the production rhythm. The invention is suitable for the manufacture of 1960MPa-level bridge cables and is beneficial to improving the risk of wire breakage and the current situation of unqualified torsion in the wire drawing process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hot-rolled wire rods, and specifically relates to a high-strength multi-phase hot-rolled wire rod for 1960MPa-grade bridge cables and a manufacturing method thereof. Background Art

[0002] With the construction of large-span bridges such as those across canyons, rivers and seas, the consumption of bridge cable steel wire has continued to increase. With the development of steel manufacturing capabilities and wire drawing technology in wire drawing plants, the strength grade of bridge cable steel wire has gradually increased to 1960MPa. Bridge cable steel wire is made of hot-rolled wire rod as the base material and is manufactured through processes such as unwinding, pickling, drawing, galvanizing, and stranding. Therefore, the manufacture of higher-strength hot-rolled wire rod is of great significance to improving the performance grade of bridge cable steel wire and achieving lightweight bridge cables. At present, the mainstream steel 1960MPa grade bridge cable hot-rolled wire rod adopts alloy steel with carbon content ≥0.87%, combined with Stelmor air-cooled line controlled cooling process for production. For example: Patent CN105671443B discloses 1960MPa grade cable galvanized steel wire hot-rolled wire rod and production method, adopts C-Si-Mn-Cr-Al-V composition design, combined with low temperature rolling and spinning after Stelmor strong air cooling process to obtain high sorbite content wire rod, reaching wire rod tensile strength ≥1320MPa, but due to the increase of carbon content and alloy content, the risk of abnormal organization such as carbon and martensite in 1960MPa grade bridge cable hot-rolled wire rod mesh will continue to rise, resulting in increased risk of wire breakage in the wire drawing process and unqualified torsion test, so the manufacturing of higher strength, better wire drawing and torsion performance of hot-rolled wire rod still has the following technical difficulties:

[0003] First, carbon is an effective and cheap strengthening element for improving the strength of wire rod. Its content is relatively high in 1960MPa grade hot rolled wire rod for bridge cables. However, it will also aggravate the tendency of central carbon segregation in the steel billet. In order to further obtain refined austenite grains to strengthen the matrix, the rolling and wire drawing will adopt lower temperatures. However, on the one hand, due to the influence of low temperature wire drawing and the maximum cooling capacity of the Stelmor air cooling line, the wire rod cooling rate can only reach 10℃ / s. The wire rod passes through the secondary cementite precipitation interval of 700~800℃. The longer the rolling and spinning temperature, the easier it is to precipitate a network of carbide structures along the austenite grain boundaries due to carbon segregation, which reduces the continuity between the lattices, reduces the toughness of the wire rod, increases its brittleness, and increases the risk of wire breakage during subsequent drawing. On the other hand, lower rolling and spinning temperatures also make the wire rod more resistant to deformation, which will increase the load and wear of the rolling line, and is not conducive to rapid rolling. Reducing the carbon content or increasing the rolling and spinning temperature will result in a certain loss of strength. At the same time, limited by the air cooling capacity, the online time of the wire rod is too extended, which is not conducive to efficient production.

[0004] Second, in order to improve the strength of the wire rod, the content of hardenability elements such as Mn and Cr in the composition is relatively high, which will also aggravate the segregation of alloy elements during the solidification process of the billet. In order to minimize the formation of network carbides and promote the refinement of pearlite lamellae to obtain fine pearlite, i.e., troostite structure, strong wind cooling treatment will be adopted after spinning. However, the increase in air volume also makes factors such as wind temperature, wind speed, and wind direction more uncontrollable, which further increases the temperature difference between the windward side and the leeward side of the wire rod, the overlap and non-overlap, and the edge of the cross section to the core. In addition, due to the segregation of hardenability elements, some over-cooled positions of the wire rod are more likely to form abnormal bainite or martensite structures that are unfavorable for drawing. The distortion and dislocation density of the abnormal structure are high and the transformation is uncontrollable, resulting in a surge in the brittleness and mechanical property fluctuations of the wire rod, which in turn causes wire breakage and torsion test failures during the wire drawing process.

[0005] 3. In order to extend the time that the wire rod passes through the pearlite phase transformation temperature range as much as possible, so as to increase the inoculation of sorbite structure and obtain higher matrix strength and drawing performance, the fan air volume and wire rod cooling speed phase transformation treatment will be adopted. However, due to the minimum cooling capacity of the Stelmor air cooling line, even if insulation or delayed cooling is adopted, the wire rod is in continuous cooling. On the one hand, although the trace V element that plays a precipitation strengthening role is added, the wire rod cooling rate is still fast, and the time that the wire rod passes through the peak precipitation temperature of sorbite or vanadium-containing carbide is short, which will limit the formation of sorbite structure and affect the refinement of the second precipitation phase. and a large amount of precipitation, thereby losing matrix strength and limiting the improvement of wire rod strength; on the other hand, the increase of alloying elements slows down the diffusion activity of carbon, the cooling capacity of the air-cooled wire makes the cementite lamellae coarser, and the wire rod is at a lower temperature after phase transformation incubation, and the thermal driving force is insufficient, which will cause large residual stress inside the organization. The troostite structure with high dislocation density reduces the plasticity of the matrix and causes obvious drawing hardening. Therefore, although the strength of the steel wire can be further improved during the deep drawing process, the plasticity loss is large and fast, and the wire breakage during drawing is aggravated, affecting the steel wire yield and efficient production. Summary of the invention

[0006] The present invention aims to solve at least one of the above-mentioned technical problems to a certain extent. The present invention provides a high-strength multi-phase hot-rolled wire rod for 1960MPa-level bridge cables and a manufacturing method thereof, which can take into account the plasticity of the wire rod and further improve the strength and organizational uniformity of the wire rod, thereby improving the production rhythm. The wire rod is suitable for the manufacture of 1960MPa-level bridge cables, and is beneficial to improving the risk of wire breakage and the current situation of unqualified torsional properties in the wire drawing process.

[0007] The technical solution adopted by the present invention to solve its technical problem is:

[0008] A method for manufacturing a 1960MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables, the manufacturing method comprising:

[0009] The wire is produced by rolling according to the chemical composition of the hot-rolled wire rod, wherein the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.86%~0.90%, Si: 0.55%~0.69%, Mn: 0.75%~0.90%, Cr: 0.15%~0.33%, V: 0.02%~0.03%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; the wire rod is rolled at a spinning temperature of ≥940°C After being spun into wire rods, they are subjected to online molten salt rapid quenching treatment, so that the wire rods first pass through the front section of molten salt and are cooled at a cooling rate of ≥37°C / s, entering the sorbite phase region from the austenite state, promoting the transformation of part of the austenite to the sorbite, and then undergoing the rear section of molten salt cooling isothermal treatment to promote the bainite phase transformation and isothermal tempering, and finally undergo roller slow cooling to produce a hot-rolled wire rod with a microstructure including 41% to 49% tempered bainite by volume and the rest being a complex phase structure composed of tempered sorbite.

[0010] The design basis of the chemical composition and mass percentage of the above hot rolled wire rod includes:

[0011] (1) Carbon: As an effective carbide strengthening element and austenite forming element, C is cheaper than other alloying elements. With the increase of carbon content, more cementite lamellae can be formed, which is beneficial to the formation of refined troostite lamellae and the promotion of bainite phase transformation, thereby improving the strength of wire rod. However, with the increase of carbon content in hypereutectoid steel, it will promote the central segregation during the solidification process of the alloy, increase the tendency of decarburization and precipitation of brittle proeutectoid network cementite, affect the drawing and torsion properties, increase the difficulty of softening the complex phase structure, and promote the short-term tempering of the structure during the subsequent molten salt cooling isothermal treatment. Therefore, in order to take into account the high strength requirements of 1960MPa grade bridge cables, regulate the peak precipitation temperatures of troostite and bainite, and reduce the softening difficulty, the mass percentage of C is controlled to be 0.86%~0.90%.

[0012] (2) Silicon: The Si element is often used as a deoxidizer in the smelting process. It can play a role in solid solution strengthening and inhibit the coarsening of cementite, so that a finer troostite structure can be obtained in the previous molten salt treatment. It can accelerate the diffusion rate of carbon, which is beneficial to increase the isothermal tempering softening rate of troostite and bainite, promote short-term rapid tempering in the subsequent molten salt treatment, and reduce the strength loss in the subsequent hot-dip galvanizing process after the wire rod is drawn into steel wire. However, too high a silicon content will make the steel easier to decarburize when heated at high temperature, prolong the transformation time in the phase change process, and reduce the toughness of the steel. Therefore, the mass percentage of Si is controlled to be 0.55%~0.69%.

[0013] (3) Manganese: Mn can be added as a deoxidizer in the steelmaking process, mainly playing a role in solid solution strengthening, while increasing the hardenability and austenite stability of the wire rod, reducing the phase transition temperature, and thus promoting the rapid nucleation of the troostite structure with fine interlamellar spacing and the dispersion precipitation of V-containing carbides during the front-end molten salt treatment. It can promote the bainite transformation during the back-end molten salt treatment, thereby improving the matrix strength. However, if the Mn content is too high, it will increase the overheating sensitivity of the steel and the central alloy element segregation of the billet, increase the risk of martensite precipitation in the core of the wire rod, and reduce the diffusion activity of carbon. It is not conducive to promoting the rapid short-term tempering softening of troostite and pearlite during the back-end molten salt treatment, thereby losing the plasticity of the wire rod. Therefore, in order to take into account the high strength and plasticity and uniformity of the hot-rolled wire rod, the mass percentage of Mn is controlled to be 0.75%~0.90%.

[0014] (4) Chromium: Cr is a medium-strong carbide-forming element in high carbon steel. It can improve the stability of austenite and the hardenability of wire rod, shift the continuous cooling transformation curve of steel to the right, and thus refine the interlamellar spacing, improve the drawing processing performance. The presence of Cr in the cementite lamellae can improve the matrix strength, facilitate large drawing deformation and reduce the strength loss during the subsequent hot-dip galvanizing process of steel wire. However, too high Cr content will aggravate component segregation, increase the risk of abnormal microstructure precipitation, reduce the activity of carbon in steel, and be unfavorable for short-term tempering softening during the subsequent molten salt treatment, resulting in increased difficulty in improving plasticity. Therefore, the mass percentage of Cr is controlled to be 0.15%~0.33%.

[0015] (5) Vanadium: As a microalloying element, V can promote grain refinement and improve the strength and toughness of steel. At the same time, it can be dispersed and precipitated in the medium temperature range of 500~600℃. Combined with the previous molten salt treatment, it can precipitate in large quantities to increase the matrix strength and provide hydrogen traps to improve the hydrogen embrittlement resistance of the wire rod. However, due to the high price of V, excessive addition will lead to an increase in the cost of the wire rod. The mass percentage of V is controlled to be 0.02%~0.03%.

[0016] (6) Phosphorus and sulfur: P and S are impurity elements. The lower the better. Therefore, P is controlled to be ≤ 0.015% and S is ≤ 0.015%.

[0017] The hot-rolled wire rod adopts C-Si-Mn-Cr-V composition design. By optimizing the proportion of each component and regulating the peak precipitation temperature of troostite and bainite, favorable conditions are provided for controlling the large-scale dispersion precipitation of V-containing carbides during the troostite phase transformation and for short-time tempering at a high temperature during the bainite phase transformation. On this basis, a higher spinning temperature is selected to promote the wire rod to be in a high-temperature austenite state, avoiding the formation of network carbides in the spinning stage caused by too low spinning temperature, and forming a large temperature gradient after molten salt treatment, thereby providing favorable conditions for refining cementite lamellae. After spinning, the wire rod is further directly subjected to online molten salt rapid quenching treatment:

[0018] First, compared with the Stelmor air-cooled line, which has limited maximum cooling capacity and is difficult to control network carbides, causing cementite lamellae to coarsen and weaken the strengthening effect, the wire rod can use the high heat exchange capacity of the molten salt after the front-stage molten salt treatment to promote the rapid cooling of the wire rod from the high-temperature austenite state. On the one hand, it can quickly skip the network carbide precipitation temperature range of 700~800℃, avoid the network carbides precipitated along the grain boundary due to carbon segregation, thereby improving the uniformity of the organization and avoiding increasing the brittleness of the wire rod. At the same time, rapid cooling is used to shorten the online time of wire rod cooling control to improve production efficiency; on the other hand, it can form a large temperature gradient and supercooling through rapid cooling, promote the transformation of part of the high-temperature austenite structure in the wire rod to troostite with finer interlamellar spacing, refine the cementite lamellae, improve the matrix strength, and reduce the softening difficulty, which provides favorable conditions for the short-term isothermal tempering and accelerated production rhythm in the later molten salt treatment.

[0019] Second, compared with the Stelmor air-cooled line, which is difficult to control abnormal tissues and causes increased fluctuations in mechanical properties due to the uncontrollable cooling rate, when the wire rod passes through the molten salt, the molten salt can cover the surface of the wire rod for rapid and uniform heat exchange, and there is no temperature difference problem between the windward side and the leeward side. It can reduce the temperature difference in the same circle of the wire rod and the temperature difference from the upper edge to the core of the cross section. On the one hand, it can promote the wire rod to quickly cool down from the high-temperature austenite state into the troostite phase region, promote the phase transformation of part of the austenite to form a troostite structure dominated by fine lamellar spacing, and at the same time extend the time when the wire rod is at the peak precipitation temperature of troostite and V-containing carbides, promote the troostite phase transformation and form a large number of dispersed precipitated V-containing carbides, and fully develop On the other hand, when the temperature of the rear molten salt is lower than that of the front molten salt, the wire rod can be cooled to the same temperature as the molten salt of the rear molten salt, thereby prolonging the bainite phase transformation time, controlling the untransformed high-temperature austenite to quickly transform into bainite structure, and forming a mixed structure of troostite and bainite, so that the formation and proportion of bainite structure, which is conventionally regarded as an abnormal structure, are more controllable, avoiding the formation of abnormal martensite structure that is unfavorable for drawing due to overcooling of the wire rod or residual austenite, effectively improving the uniformity of the structure, and being beneficial to reducing wire breakage during drawing and improving torsional performance. At the same time, on the basis of not excessively adding alloy content, part of the bainite structure is used to further improve the matrix strength.

[0020] 3. Compared with the Stelmor air-cooled line, which has limited minimum cooling capacity and continuous cooling, and has insufficient plasticity and cannot improve the bainite brittleness, the wire rod can be consistent with the molten salt temperature after passing through the latter molten salt, that is, it maintains a higher processing temperature and isothermal state, and will not cause the coarsening of V-containing carbides due to excessively high temperature for a longer time. While promoting the transformation of the wire rod into a bainite structure, it can promote the short-term tempering of the mixed structure of troostite and bainite, weaken the bainite brittleness, and transform it into a tempered bainite that is both strong and tough, quickly reduce the tissue stress and dislocation density, so as to improve the strength-plasticity matching of the wire rod. After that, the wire rod is slowly cooled by a roller, which can continue the high temperature state of the wire rod through slow cooling, promote further toughening of the wire rod structure, improve the softening effect of the wire rod, and effectively utilize the bainite structure that is conventionally regarded as abnormal, to obtain a complex phase structure that takes into account plasticity, strength and higher tissue uniformity, thereby meeting the manufacturing and application needs of 1960MPa-level bridge cables.

[0021] Due to the high alloy content and high spinning temperature in the composition, selecting appropriate heating furnace soaking temperature and furnace time can promote uniform diffusion of alloy components, reduce segregation, control decarburization and prepare for controlling rolling temperature. In a preferred embodiment, before rolling, the heating furnace soaking temperature is controlled to be 1140~1180℃ and the furnace time is 90~150min.

[0022] Since the spinning temperature is relatively high, appropriate rolling temperature and deformation are selected to avoid aggravating the wear of the rolling line due to too low rolling temperature, and to avoid the growth of austenite grains due to too high rolling temperature. While increasing the rolling speed, dynamic recrystallization is promoted during the final rolling process, decarburization is controlled, grains are refined, and the matrix is ​​strengthened and toughened. In a preferred embodiment, during the rolling, the initial rolling temperature is controlled to be 1100~1140℃, the final rolling temperature is 960~1000℃, and the final rolling reduction is 30%~35%.

[0023] The molten salt temperature of the front-stage molten salt is in the sorbite phase region temperature. The lower the molten salt temperature and the longer the treatment time, the more it can promote the refinement of sorbite lamellae and sorbite nucleation, reduce the difficulty of sorbite tempering softening during the rear-stage molten salt treatment, and provide more power for the large-scale dispersion and precipitation of V-containing carbides. However, if the molten salt temperature is too low and the treatment time is too long, the high-temperature austenite in the organization will transform too much into sorbite, which will affect the proportion of bainite phase transformation during the rear-stage molten salt treatment, thereby losing the matrix strength. At the same time, too low a molten salt temperature is not conducive to the precipitation of V. On the contrary, the higher the molten salt temperature and the shorter the treatment time, the less austenite will transform into sorbite. Subsequent bainite phase transformation will increase, causing the plasticity of the matrix to decrease. However, if the molten salt temperature is too high and the treatment time is too short, the troostite lamellae will become coarser, increasing the difficulty of isothermal tempering, which is not conducive to drawing. It is also not conducive to the precipitation of dispersed precipitates in the crystal, causing a decrease in the proportion of tempered troostite and resulting in a loss of plasticity and toughness. Therefore, the molten salt temperature and treatment time of the front-stage molten salt can be further controlled to control the transformation of part of the austenite to a troostite structure dominated by fine lamellae spacing, so as to make organizational preparations for the rear-stage molten salt treatment. In a preferred embodiment, the molten salt temperature of the front-stage molten salt is 550~580℃, and the treatment time is 5~20s.

[0024] Since the wire rod cooling rate is fast and the temperature gradient is large during the front-stage molten salt treatment, selecting a higher molten salt circulation rate can further control the molten salt temperature rise, promote the nucleation of the troostite structure, and further improve the uniformity of the structure. In a preferred embodiment, the molten salt circulation rate of the front-stage molten salt is 440~640t / h, and the molten salt temperature rise is ≤10℃.

[0025] The molten salt temperature of the rear-stage molten salt is lower than that of the front-stage molten salt. The lower the molten salt temperature of the rear-stage molten salt and the longer the treatment time, the faster the transformation of the untransformed high-temperature austenite to bainite can be promoted. At the same time, as the treatment time increases, the tempering of troostite and bainite can be promoted, the brittleness of the organization can be weakened, and the plasticity of the wire rod can be improved. However, if the molten salt temperature is too low, the softening thermal power will be reduced, which is not conducive to promoting short-term tempering of the organization and accelerating the production rhythm, and there is even a risk of producing abnormal martensitic organization. On the contrary, the higher the molten salt temperature of the rear-stage molten salt is, the more driving force can be provided for the tempering softening of the organization and the softening of the organization can be promoted. However, if the molten salt temperature is too high, it will have a negative impact on bainite. Unfavorable transformation of the bainite structure will affect the matrix strength and mechanical property fluctuations. If the processing time is too short, it will affect the bainite phase transformation and increase the risk of abnormal martensite structure in the subsequent cooling process. At the same time, the softening effect will be weakened, which will increase the brittleness of the wire rod. Therefore, the molten salt temperature and processing time of the rear-stage molten salt can be further controlled to promote the rapid phase transformation of bainite. At the same time, it can promote the short-term tempering of the mixed structure of troostite and bainite, weaken the brittleness of bainite, improve the strength-plasticity matching of the wire rod and speed up the production rhythm. In a preferred embodiment, the molten salt temperature of the rear-stage molten salt is 400~445℃, and the processing time is 50~80s.

[0026] Since the temperature difference between the front-stage molten salt and the rear-stage molten salt is relatively small, the molten salt circulation rate can be appropriately reduced. While controlling the molten salt temperature rise and processing accuracy, the production energy consumption can be appropriately reduced. In a preferred embodiment, the molten salt circulation rate of the rear-stage molten salt is 260~360t / h, and the molten salt temperature rise is ≤3°C.

[0027] In a preferred embodiment, the roller slow cooling controls the wire rod to cool at a cooling rate of 0.15~0.3℃ / s for 150~200s, so that after the wire rod comes out of the salt bath at 400~450℃, it can be slowly cooled at a lower cooling rate to continue the tempering softening effect, promote further toughening of the structure, reduce dislocation density, and then coil it.

[0028] In a preferred embodiment, the roller slow cooling adopts the hot air controlled wire rod cooling of the online molten salt rapid quenching treatment, which can recycle the hot air thermal energy generated during the online molten salt rapid quenching treatment, further reduce production energy consumption, and avoid the low cooling speed causing the wire rod conveying speed to be too low, affecting production efficiency.

[0029] A 1960MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables, wherein the hot-rolled wire rod is manufactured by any one of the above-mentioned methods for manufacturing the 1960MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables.

[0030] The above-mentioned hot-rolled wire rod is designed with V-containing hypereutectoid chemical composition and organizational regulation. Compared with the wire rod organization with a high sorbitization rate of traditional wire rod for bridge cables, the wire rod includes a complex phase organization formed by tempered sorbite and tempered bainite. On the one hand, the distortion and dislocation density of bainite are higher than those of sorbite. After controllable phase transformation into tempered bainite that is both strong and tough, the high-strength characteristics of bainite can be retained, and higher matrix strength can be provided in combination with the dispersed precipitation strengthening phase of sorbite and V. On the other hand, after the sorbite is transformed into tempered sorbite by short-time tempering, the organizational stress and dislocation density are further reduced. After the bainite obtained by rapid quenching is transformed into tempered bainite by short-time tempering, the brittleness of bainite can be weakened, thereby improving the strength-plasticity matching of the wire rod, so that it can be used for the manufacture of 1960MPa-level bridge cables and reduce the risks of wire making and torsional cracking.

[0031] The finer the interlamellar spacing of the tempered troostite, the more beneficial it is to improving the matrix strength. However, too fine an interlamellar spacing is accompanied by a decrease in the temperature of the molten salt in the front stage, an increase in the proportion of tempered troostite and the energy consumption of the molten salt cycle, which affects the bainite phase transformation. Therefore, in a preferred embodiment, the interlamellar spacing of the tempered troostite is 85~130nm.

[0032] In a preferred embodiment, the network carbide level of the hot-rolled wire rod is level 0, which can avoid the deterioration effect of the network carbide on the uniformity and plasticity of the wire rod structure and improve the drawing and torsion performance.

[0033] Since the abnormal network carbide and martensite structures of the hot-rolled wire rod are avoided, the structural uniformity is better, the fluctuation of mechanical properties is further reduced, and the risk of wire making and torsional cracking can be further reduced. In a preferred embodiment, the mechanical property difference of the hot-rolled wire rod is ≤46MPa.

[0034] In a preferred embodiment, the diameter of the hot-rolled wire rod is 8.0~15.0mm, the tensile strength is 1420~1470MPa, and the cross-sectional shrinkage rate is 39%~44%. The hot-rolled wire rod has a high tensile strength and can reach the target strength grade as soon as possible through wire drawing, reducing plastic loss in the process. At the same time, the hot-rolled wire rod has a high cross-sectional shrinkage rate, which exhibits better plasticity and toughness, and can further reduce the risk of wire breakage during drawing and torsion failure.

[0035] Compared with the prior art, the beneficial effects of the present invention are at least:

[0036] (1) In view of the fact that the existing 1960MPa grade hot-rolled wire rod for bridge cables is produced with alloy steel with a carbon content of ≥0.87%, which leads to an increasing risk of precipitation of abnormal structures such as network carbon and martensite, an increased risk of wire breakage during the wire drawing process, and failure of torsion test, the manufacturing method of the present invention combines the V-containing chemical composition design with the online molten salt rapid quenching technology. The front-stage molten salt first controls the wire rod to quickly pass through the network carbide precipitation zone from the high-temperature austenite state and enter the troostite phase region, so that part of the austenite is transformed to form a troostite structure with fine lamellar spacing as the main structure. The rear-stage molten salt controls the untransformed high-temperature austenite to quickly transform into a bainite structure, and promotes the short-term tempering of the wire rod structure, weakens the brittleness of the bainite, and transforms it to tempered bainite, thereby improving the strength and plasticity matching of the wire rod. Finally, the wire rod structure is further toughened by slow cooling through a roller, which can take into account the plasticity of the wire rod and further improve the strength and uniformity of the wire rod, avoid the precipitation of abnormal structures such as network carbon and martensite, and has good industrial adaptability.

[0037] (2) In view of the current situation that the hot-rolled wire rods for 1960MPa-class bridge cables have insufficient strength and plasticity, large fluctuations in mechanical properties, and thus the risk of wire drawing and torsion cracking, the hot-rolled wire rods of the present invention are combined with the C-Si-Mn-Cr-V composition design and the control of the complex phase structure formed by tempered troostite and tempered bainite, which can avoid abnormal structures of net carbon and martensite, making the bainite phase change, which is conventionally regarded as an abnormal structure, more controllable. After further transformation into tempered bainite that is both strong and tough, the high strength characteristics of bainite can be retained, and the dispersed precipitation strengthening phases of troostite and V can provide higher matrix strength. After the tempering state is controlled, the structural stress and dislocation density are further reduced, and the brittleness of bainite can be weakened, achieving a tensile strength of 1420~1470MPa and a cross-sectional shrinkage rate of 39%~44%. The strength-plastic matching of the wire rod is improved, the structural uniformity is better, and the fluctuation of mechanical properties is further reduced. It is suitable for the manufacture of 1960MPa-class bridge cables, which is beneficial to improving the risk of wire breakage and torsion failure in the wire drawing process.

[0038] (3) The manufacturing method of the present invention can reduce the restriction on the rolling temperature due to the higher spinning temperature, promote rapid rolling in the rolling process, and at the same time use online molten salt rapid quenching to promote rapid cooling of the wire rod, so that the production rhythm is faster, which is beneficial to improving production efficiency and has good industrial adaptability. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0040] Figure 1 is a metallographic structure diagram of Example 1 of the present invention;

[0041] Figure 2 is the metallographic structure diagram of Example 2 of the present invention;

[0042] Figure 3 It is the metallographic structure diagram of Example 3 of the present invention. DETAILED DESCRIPTION

[0043] The embodiments described below with reference to the accompanying drawings are exemplary and are only for illustration and do not limit the description of the features and characteristics of the present invention, so as to propose the best way to implement the present invention, and are intended to be used to explain the present invention and are sufficient to enable those skilled in the art to implement the present invention, but cannot be understood as any limitation on the scope of the present invention, which is limited only by the appended claims; the organization and performance testing of the hot-rolled wire rods obtained in the following embodiments and comparative examples include: the tensile test is carried out using "GB-T 228.1-2021 Metallic Material Tensile Test Part 1: Room Temperature Test Method" to obtain the tensile strength and cross-sectional reduction rate; the organization test is carried out according to the metal microstructure detection method of GB / T13298 standard; the mechanical property same circle difference test method: take 2 circles of wire rod 5m away from the end of the coil, take the overlap area position as the base point, divide each circle of wire rod into 8 sections on average, take 1 tensile specimen on each section, and the strength extreme difference of the tensile specimen after the tensile test is the mechanical property same circle difference. Embodiment 1:

[0044] A preferred embodiment of the manufacturing method of the 1960MPa grade high-strength multiphase hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.90%, Si: 0.65%, Mn: 0.90%, Cr: 0.15%, V: 0.02%, P: 0.012%, S: 0.013%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt rapid quenching → roller slow cooling → coiling, specifically:

[0045] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, control the parameters of the heating furnace to promote uniform diffusion of components in the steel billet, reduce segregation and control decarburization, and after the steel billet leaves the heating furnace, roll the steel billet into a wire with a diameter of 15mm through a rolling line, select appropriate rolling temperature and deformation, increase the rolling speed, promote dynamic recrystallization during the final rolling process, control decarburization and refine grains, specifically: control the heating furnace soaking temperature to 1155°C, and in the furnace The time is 130min, the initial rolling temperature is 1115℃, the final rolling temperature is 975℃, and the final rolling reduction is 30%; the wire-spinning process is used to make the wire rods coming out of the rolling line into wire rods through the wire-spinning mechanism, and the wire rods are spread on the rollers and transported along the rollers. A higher wire-spinning temperature is selected to promote the wire rods to be in a high-temperature austenite state, and to avoid the formation of network carbides in the wire-spinning stage due to too low a wire-spinning temperature, so as to form a large temperature gradient later, thereby providing favorable conditions for promoting the rapid nucleation of troostite with fine lamellar spacing. Specifically, the wire-spinning temperature is controlled to be 950℃.

[0046] The online molten salt rapid quenching process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for front-stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 37°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to enter the sorbite phase area, inhibiting the formation of network carbides, promoting the phase transformation of part of the austenite to form a sorbite structure with fine lamellar spacing as the main component, and promoting the large-scale dispersion and precipitation of V-containing carbides. Then, it is conveyed by a roller through the second stage salt bath tank for rear-stage molten salt treatment, reducing Low molten salt temperature and molten salt circulation volume promote the transformation of untransformed high-temperature austenite to bainite structure, perform short-time isothermal tempering, promote tempering softening of troostite and bainite, weaken the brittleness of bainite, and improve the strength-plasticity matching of wire rod. Specifically: the molten salt temperature of the front-stage molten salt is 580°C, the processing time is 5s, the molten salt circulation volume is 440t / h, and the molten salt temperature rise is ≤10°C; the molten salt temperature of the rear-stage molten salt is 400°C, the processing time is 80s, the molten salt circulation volume is 360t / h, and the molten salt temperature rise is ≤3°C.

[0047] The roller slow cooling process adopts the method of closing the insulation cover, and the conveying roller conveys the wire rod that has passed through the second salt bath tank into the insulation cover, and conveys the hot air treated by online molten salt rapid quenching into the insulation cover to control the cooling of the wire rod, promote further toughening of the wire rod structure, and improve the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to be cooled at a cooling rate of 0.15°C / s for 200s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and obtain the hot-rolled wire rod product after packaging and storage. Its metallographic structure diagram is as follows Figure 1 shown.

[0048] Comparative Example 1:

[0049] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 1 in that: the manufacturing method is manufactured according to the process flow of rolling → spinning → Stelmor air cooling, specifically: the heating furnace soaking temperature is controlled to be 1040°C, the furnace time is 200min, the initial rolling temperature is 1005°C, the final rolling temperature is 885°C, and the spinning temperature is 865°C; the Stelmor strong air cooling adopts an air volume of 260,000 m per fan 3 / h, open 1~6# fans at 80%, cool the wire rod to 675℃ at a cooling rate of 8.5℃ / s, and then open 7~14# fans at 25%, cool the wire rod to 335℃ at a cooling rate of 3.7℃ / s, and obtain the hot-rolled wire rod product after it comes off the line.

[0050] Comparative Example 2:

[0051] A method for manufacturing a hot-rolled wire rod, which differs from Example 1 in that: the heating furnace soaking temperature is controlled to be 1070°C, the furnace time is 180min, the initial rolling temperature is 1040°C, the final rolling temperature is 920°C, the spinning temperature is 900°C, during the front-stage molten salt treatment, the wire rod is cooled at a cooling rate of 32°C / s, and the hot-rolled wire rod finished product is obtained after it is off the line. Embodiment 2:

[0052] A preferred embodiment of the manufacturing method of the 1960MPa grade high-strength multiphase hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.86%, Si: 0.59%, Mn: 0.75%, Cr: 0.33%, V: 0.025%, P: 0.013%, S: 0.015%, and the rest is Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt rapid quenching → roller slow cooling → coiling, specifically:

[0053] The rolling process is used to heat a steel billet with a specification of 180mm×180mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, and control the parameters of the heating furnace to promote uniform diffusion of components in the steel billet, reduce segregation and control decarburization. After the steel billet leaves the heating furnace, it is rolled into a wire with a diameter of 8mm through a rolling line, and appropriate rolling temperature and deformation are selected to increase the rolling speed while promoting dynamic recrystallization in the final rolling process, controlling decarburization and refining grains. Specifically: the heating furnace is controlled to have a soaking temperature of 1180°C, and the furnace is heated to 1180°C. The rolling time is 115min, the initial rolling temperature is 1140℃, the final rolling temperature is 1000℃, and the final rolling reduction is 35%; the wire-spinning process is used to make the wire rods out of the rolling line through the wire-spinning mechanism into wire rods, and the wire rods are spread on the rollers and transported along the rollers. A higher wire-spinning temperature is selected to promote the wire rods to be in a high-temperature austenite state, and to avoid the formation of network carbides in the wire-spinning stage caused by too low a wire-spinning temperature, so as to form a large temperature gradient later, thereby providing favorable conditions for promoting the rapid nucleation of troostite with fine lamellar spacing. Specifically, the wire-spinning temperature is controlled to be 965℃.

[0054] The online molten salt rapid quenching process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for front-stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 38°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to enter the sorbite phase area, inhibiting the formation of network carbides, promoting the phase transformation of part of the austenite to form a sorbite structure with fine lamellar spacing as the main component, and promoting the large-scale dispersion and precipitation of V-containing carbides. It is then conveyed by a roller through the second stage salt bath tank for rear-stage molten salt treatment, reducing The molten salt temperature and the molten salt circulation volume promote the transformation of untransformed high-temperature austenite to bainite structure, perform short-time isothermal tempering, promote the tempering softening of troostite and bainite, weaken the brittleness of bainite, and improve the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature of the front-stage molten salt is 571°C, the processing time is 13s, the molten salt circulation volume is 600t / h, and the molten salt temperature rise is ≤10°C; the molten salt temperature of the rear-stage molten salt is 415°C, the processing time is 75s, the molten salt circulation volume is 320t / h, and the molten salt temperature rise is ≤3°C.

[0055] The roller slow cooling process adopts the method of closing the insulation cover, and the conveying roller conveys the wire rod passing through the second salt bath tank into the insulation cover, and conveys the hot air treated by online molten salt rapid quenching into the insulation cover to control the cooling of the wire rod, promote further toughening of the wire rod structure, and improve the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to be cooled at a cooling rate of 0.2°C / s for 185s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and obtain the hot-rolled wire rod product after packaging and storage. Its metallographic structure diagram is as follows Figure 2 shown.

[0056] Comparative Example 3:

[0057] A method for manufacturing a hot-rolled wire rod, which differs from Example 2 in that during the front-stage molten salt treatment, the wire rod is cooled at a cooling rate of 42°C / s, the molten salt temperature of the front-stage molten salt is 515°C, the treatment time is 30s, and a hot-rolled wire rod finished product is obtained after going offline.

[0058] Comparative Example 4:

[0059] A method for manufacturing a hot-rolled wire rod, which differs from Example 2 in that during the front-stage molten salt treatment, the wire rod is cooled at a cooling rate of 36°C / s, the molten salt temperature of the front-stage molten salt is 595°C, the treatment time is 5s, and a hot-rolled wire rod finished product is obtained after going offline. Embodiment 3:

[0060] A preferred embodiment of the method for manufacturing the 1960MPa grade high-strength multiphase hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.89%, Si: 0.69%, Mn: 0.77%, Cr: 0.19%, V: 0.022%, P: 0.014%, S: 0.014%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt rapid quenching → roller slow cooling → coiling, specifically:

[0061] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, control the parameters of the heating furnace to promote uniform diffusion of components in the steel billet, reduce segregation and control decarburization, and after the steel billet leaves the heating furnace, roll the steel billet into a wire with a diameter of 13mm through a rolling line, select appropriate rolling temperature and deformation, increase the rolling speed, promote dynamic recrystallization in the final rolling process, control decarburization and refine grains, specifically: control the heating furnace soaking temperature to 1140°C, and in the furnace The time is 150min, the initial rolling temperature is 1100℃, the final rolling temperature is 960℃, and the final rolling reduction is 33%; the wire-spinning process is used to make the wire rods out of the rolling line into wire rods through the wire-spinning mechanism, and the wire rods are spread on the rollers and transported along the rollers. A higher wire-spinning temperature is selected to promote the wire rods to be in a high-temperature austenite state, and to avoid the formation of network carbides in the wire-spinning stage caused by too low a wire-spinning temperature, so as to form a large temperature gradient later, thereby providing favorable conditions for promoting the rapid nucleation of troostite with fine lamellar spacing. Specifically, the wire-spinning temperature is controlled to be 940℃.

[0062] The online molten salt rapid quenching process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for front-stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 37°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to enter the sorbite phase area, inhibiting the formation of network carbides, promoting the phase transformation of part of the austenite to form a sorbite structure with fine lamellar spacing as the main component, and promoting the large-scale dispersion and precipitation of V-containing carbides. It is then conveyed by a roller through the second stage salt bath tank for rear-stage molten salt treatment, reducing The molten salt temperature and the molten salt circulation volume promote the transformation of untransformed high-temperature austenite to bainite structure, perform short-time isothermal tempering, promote the tempering softening of troostite and bainite, weaken the brittleness of bainite, and improve the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature of the front-stage molten salt is 563°C, the processing time is 16s, the molten salt circulation volume is 500t / h, and the molten salt temperature rise is ≤10°C; the molten salt temperature of the rear-stage molten salt is 430°C, the processing time is 65s, the molten salt circulation volume is 290t / h, and the molten salt temperature rise is ≤3°C.

[0063] The roller slow cooling process adopts the method of closing the insulation cover, and the conveying roller conveys the wire rod that has passed through the second salt bath tank into the insulation cover, and conveys the hot air treated by online molten salt rapid quenching into the insulation cover to control the cooling of the wire rod, promote further toughening of the wire rod structure, and improve the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to be cooled at a cooling rate of 0.25°C / s for 165s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and obtain the hot-rolled wire rod product after packaging and storage. Its metallographic structure diagram is as follows Figure 3 shown.

[0064] Comparative Example 5:

[0065] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 3 in that the molten salt temperature of the rear-stage molten salt is 380° C., the processing time is 45 seconds, and a hot-rolled wire rod finished product is obtained after going offline.

[0066] Comparative Example 6:

[0067] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 3 in that the molten salt temperature of the rear-stage molten salt is 480° C., the processing time is 125 s, and a hot-rolled wire rod finished product is obtained after the production line is off the line. Embodiment 4:

[0068] A preferred embodiment of the manufacturing method of the 1960MPa grade high-strength multiphase hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.88%, Si: 0.55%, Mn: 0.82%, Cr: 0.29%, V: 0.03%, P: 0.015%, S: 0.011%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt rapid quenching → roller slow cooling → coiling, specifically:

[0069] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, control the parameters of the heating furnace to promote uniform diffusion of components in the steel billet, reduce segregation and control decarburization, and after the steel billet leaves the heating furnace, roll the steel billet into a wire with a diameter of 11mm through a rolling line, select appropriate rolling temperature and deformation, increase the rolling speed, promote dynamic recrystallization in the final rolling process, control decarburization and refine grains, specifically: control the heating furnace soaking temperature to 1165°C, and in the furnace The time is 90min, the initial rolling temperature is 1130℃, the final rolling temperature is 985℃, and the final rolling reduction is 31%; the wire-spinning process is used to make the wire rods coming out of the rolling line into wire rods through the wire-spinning mechanism, and the wire rods are spread on the rollers and transported along the rollers. A higher wire-spinning temperature is selected to promote the wire rods to be in a high-temperature austenite state, and to avoid the formation of network carbides in the wire-spinning stage caused by too low a wire-spinning temperature, so as to form a large temperature gradient later, thereby providing favorable conditions for promoting the rapid nucleation of troostite with fine lamellar spacing. Specifically, the wire-spinning temperature is controlled to be 955℃.

[0070] The online molten salt rapid quenching process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for front-stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 39°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to enter the sorbite phase area, inhibiting the formation of network carbides, promoting the phase transformation of part of the austenite to form a sorbite structure with fine lamellar spacing as the main component, and promoting the large-scale dispersion and precipitation of V-containing carbides. It is then conveyed by a roller through the second stage salt bath tank for rear-stage molten salt treatment, reducing The molten salt temperature and the molten salt circulation volume promote the transformation of untransformed high-temperature austenite to bainite structure, perform short-time isothermal tempering, promote the tempering softening of troostite and bainite, weaken the brittleness of bainite, and improve the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature of the front-stage molten salt is 550°C, the processing time is 20s, the molten salt circulation volume is 640t / h, and the molten salt temperature rise is ≤10°C; the molten salt temperature of the rear-stage molten salt is 445°C, the processing time is 50s, the molten salt circulation volume is 260t / h, and the molten salt temperature rise is ≤3°C.

[0071] The roller slow cooling process adopts the method of closing the insulation cover, and the conveying roller conveys the wire rod passing through the second salt bath tank into the insulation cover, and conveys the hot air treated by online molten salt rapid quenching into the insulation cover to control the cooling of the wire rod, promote further toughening of the wire rod structure, and improve the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to be cooled at a cooling rate of 0.3°C / s for 150s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and obtain the hot-rolled wire rod product after packaging and storage. Its metallographic structure diagram is as follows Figure 1 shown.

[0072] Comparative Example 7:

[0073] A method for manufacturing a hot-rolled wire rod, which differs from Example 4 in that: the method is manufactured according to the process flow of rolling → spinning → online molten salt rapid quenching → air cooling, and the air cooling adopts a heat preservation cover to open, and the wire rod is controlled to be cooled to 350°C at a cooling rate of 1.4°C / s. After the hot-rolled wire rod is off the line, the finished product is obtained. After testing, the tensile strength is 1452MPa and the cross-sectional shrinkage rate is 36%.

[0074] The hot rolled wire rods obtained in the above examples 1 to 4 and comparative examples 1 to 6 were subjected to microstructure and performance tests, and the obtained comparative results are shown in Table 1 below:

[0075] Table 1. Comparison of microstructure and performance of hot rolled wire rods with different compositions and manufacturing methods

[0076]

[0077] From the comparison results of Example 1 and Comparative Example 1, it can be seen that compared with the Stelmor air-cooled wire treatment under the C-Si-Mn-Cr-V component system, the strengthening effect is often weakened due to the uncontrollable cooling rate during the cooling phase transformation process, and abnormal structures such as network carbon and martensite are generated, the fluctuation of mechanical properties increases, and the risk of wire breakage and torsion test failure in the wire drawing process increases. The present invention combines the online molten salt rapid quenching technology, and the front-stage molten salt first controls the wire rod to quickly enter the troostite phase region from the high-temperature austenite state, so that part of the austenite is transformed into The hot-rolled wire rod is formed into a bainite structure with mainly fine lamellar spacing, and then the untransformed high-temperature austenite is quickly transformed into a bainite structure under the control of the molten salt in the later stage, and the wire rod structure is promoted to be tempered for a short time, which can effectively avoid abnormal structures of network carbon and martensite and improve the strength-plasticity matching of the wire rod. It can be seen from the results of Examples 1 to 4 that the hot-rolled wire rod can achieve a tensile strength of 1420 to 1470 MPa and a cross-sectional shrinkage rate of 39% to 44%, which is suitable for the manufacture of 1960 MPa-level bridge cables, and is beneficial to improving the risk of wire breakage in the wire drawing process and the current situation of unqualified torsional bending.

[0078] From the comparison results of Example 1 and Comparative Example 2, it can be seen that a higher spinning temperature is selected to promote the wire rod to be in a high-temperature austenite state, avoid the formation of network carbides in the spinning stage caused by too low spinning temperature, and form a larger temperature gradient after molten salt treatment to provide favorable conditions for refining the cementite lamellae, and can also reduce the restriction on the rolling temperature, so as to increase the rolling temperature, reduce the deformation resistance of the wire rod, and promote rapid rolling during the rolling process.

[0079] From the comparison results of Example 2 and Comparative Example 3, it can be seen that the lower the molten salt temperature of the front-stage molten salt and the longer the treatment time, the refinement of the troostite lamellae and the nucleation of the troostite can be promoted, the difficulty of tempering and softening of the troostite during the rear-stage molten salt treatment can be reduced, and more power can be provided for the large-scale dispersion and precipitation of V-containing carbides. However, if the molten salt temperature is too low and the treatment time is too long, the high-temperature austenite in the organization will transform too much into troostite, which will affect the proportion of bainite phase transformation during the rear-stage molten salt treatment, and thus lose the matrix strength.

[0080] From the comparison results of Example 2 and Comparative Example 4, it can be seen that the higher the molten salt temperature of the front stage molten salt and the shorter the treatment time, the less the transformation of austenite to troostite, the more subsequent bainite phase transformation will increase, and the plasticity of the matrix will decrease. However, if the molten salt temperature is too high and the treatment time is too short, the troostite lamellae will become coarser, increasing the difficulty of isothermal tempering, and it will also be unfavorable for the precipitation of dispersed precipitate phases in the crystal, causing a decrease in the proportion of tempered troostite and resulting in a loss of plasticity and toughness.

[0081] From the comparison results of Example 3 and Comparative Example 5, it can be seen that the lower the molten salt temperature of the rear-stage molten salt and the longer the treatment time, the faster the transformation of the untransformed high-temperature austenite to bainite can be promoted. However, if the molten salt temperature is too low, the softening thermodynamic force will be reduced. As the treatment time becomes shorter, not only is the softening insufficient, but there is even a risk of insufficient phase transformation of bainite and the generation of abnormal martensite structure, which will increase the brittleness of the wire rod and seriously affect the plasticity of the wire rod.

[0082] From the comparison results of Example 3 and Comparative Example 6, it can be seen that the higher the molten salt temperature of the latter stage molten salt, the more driving force can be provided for the tempering softening of the structure and promote the softening of the structure. However, if the molten salt temperature is too high, it is not conducive to the transformation of the bainite structure, which will affect the matrix strength and mechanical property fluctuations. As the processing time becomes longer, the wire rod will be too softened, which will lead to insufficient matrix strength.

[0083] From the comparison results of Example 4 and Comparative Example 7, it can be seen that by slowly cooling to continue the high temperature state of the wire rod, the wire rod structure can be further toughened and the softening effect of the wire rod can be improved.

[0084] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for manufacturing a 1960MPa grade high-strength multiphase hot-rolled wire rod for bridge cables, characterized in that: The manufacturing method thereof comprises: The wire is produced by rolling according to the chemical composition of the hot-rolled wire rod, wherein the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.86%~0.90%, Si: 0.55%~0.69%, Mn: 0.75%~0.90%, Cr: 0.15%~0.33%, V: 0.02%~0.03%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; the wire rod is rolled at a spinning temperature of ≥940°C After the wire rod is spun, it is subjected to online molten salt rapid quenching treatment, so that the wire rod first passes through the front section of molten salt and is cooled at a cooling rate of ≥37°C / s, enters the sorbite phase region from the austenite state, promotes the transformation of part of the austenite to the sorbite, and then undergoes the rear section of molten salt cooling isothermal treatment to promote the bainite phase transformation and isothermal tempering, and finally passes through roller slow cooling to obtain a hot rolled wire rod with a microstructure including 41% to 49% tempered bainite by volume and the rest being a tempered sorbite multiphase structure; The molten salt temperature of the front-stage molten salt is 550-580°C, and the processing time is 5-20s; the molten salt temperature of the rear-stage molten salt is 400-445°C, and the processing time is 50-80s. The roller slow cooling controls the wire rod to cool at a cooling rate of 0.15-0.3°C / s for 150-200s.

2. The method for manufacturing 1960MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 1, characterized in that: Before the rolling, the heating furnace is controlled to have a soaking temperature of 1140-1180° C. and a furnace time of 90-150 min.

3. The method for manufacturing 1960MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 1, characterized in that: During the rolling, the initial rolling temperature is controlled to be 1100-1140° C., the final rolling temperature is controlled to be 960-1000° C., and the final rolling reduction is controlled to be 30%-35%.

4. The method for manufacturing 1960MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 1, characterized in that: The molten salt circulation rate of the front-stage molten salt is 440-640 t / h, and the molten salt temperature rise is ≤10°C; the molten salt circulation rate of the rear-stage molten salt is 260-360 t / h, and the molten salt temperature rise is ≤3°C.

5. The method for manufacturing 1960MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 1, characterized in that: The roller slow cooling adopts hot air controlled wire rod cooling after online molten salt rapid quenching treatment.

6. A 1960MPa grade high-strength multiphase hot-rolled wire rod for bridge cables, characterized in that: The hot-rolled wire rod is manufactured by the method for manufacturing 1960MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables as described in any one of claims 1 to 5.

7. The 1960MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 6, characterized in that: The interlamellar spacing of the tempered bainite is 85-130 nm, the network carbide grade of the hot-rolled wire rod is grade 0, and the mechanical property difference is ≤46 MPa.

8. The 1960MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 6, characterized in that: The hot-rolled wire rod has a diameter of 8.0-15.0 mm, a tensile strength of 1420-1470 MPa, and a cross-sectional shrinkage of 39%-44%.

Citation Information

Patent Citations

  • Hot-rolled wire rods for 1960 MPa-class cable galvanized steel wires and production method

    CN105671443B

  • Cold heading steel wire rod for 15.9-grade non-quenched and tempered bolt and manufacturing method of cold heading steel wire rod

    CN118653094A

  • High-plasticity hot-rolled carbon wire rod for 1670 MPa bridge cable and manufacturing method of high-plasticity hot-rolled carbon wire rod

    CN118854174A

  • High-strength economical high-carbon steel wire rod and manufacturing method therefor

    WO2024213156A1